2020
DOI: 10.3390/microorganisms8030329
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Lactobacillus helveticus D75 and D76 Confirms Safety and Probiotic Potential

Abstract: Whole-genome DNA sequencing of Lactobacillus D75 and D76 strains (Vitaflor, Russia) was determined using the PacBio RS II platform, which was followed by de novo assembly with SMRT Portal 2.3.0. The average nucleotide identity (ANI) test showed that both strains belong to the Lactobacillus helveticus, but not to the L. acidophilus, as previously assumed. In addition, 31 exopolysaccharide (EPS) production genes (nine of which form a single genetic cluster), 13 adhesion genes, 38 milk protein and 11 milk sugar u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…A study indicated that L. helveticus D75 and D76 are capable of producing the bacteriocin, which could destroy the membrane potential of target cells [47]. In our study, four genes existed to code bacteriocin.…”
Section: Discussionmentioning
confidence: 70%
“…A study indicated that L. helveticus D75 and D76 are capable of producing the bacteriocin, which could destroy the membrane potential of target cells [47]. In our study, four genes existed to code bacteriocin.…”
Section: Discussionmentioning
confidence: 70%
“…L. brevis MYSN105 was comprehensively studied for potential probiotic traits using whole-genome sequence analysis, which enabled identifying genes linked to safety and antimicrobial properties. Several studies have reported Lactobacillus species consisting of genes related to their stress resistance, antimicrobial properties, and other functional mechanisms ( Chen et al, 2019 ; Toropov et al, 2020 ). The genomic finding suggests that understanding the functional and genetic characteristics could provide new insights into applications in gut health and animal feed additives ( Heo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first complete LAB genome sequence was published in 2001 for the species Lactococcus lactis IL1403 (Bolotin GenBank (Yanwei et al, 2022) enabling for a comprehensive understanding of the industrial application and metabolic characteristics of LAB. Whole genome information can reflect the safety of LAB strains by assessing genes related to drug resistance, virulence, and pathogenicity and determining whether the related genes can be transmitted horizontally (Rodrıǵuez-Serrano et al, 2018;Toropov et al, 2020;Zhou et al, 2021). Furthermore, the genomescale metabolic model (GSMM) can be reconstructed from wholegenome data to simulate and anticipate how bacteria will behave in each environment and to systematically direct metabolic engineering efforts.…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…For example, Linares-Morales et al ( 2020) reported encouraging results of E. faecium against post-harvest pathogens, however, further evaluation of the strains' safety is necessary as some of the Enterococcus strains can potentially carry harmful genes (Venegas-Ortega et al, 2020). The increased efficiency of genome analysis over the past decade allows screening on the safety of LAB strains by assessing genes related to drug resistance, virulence, and pathogenicity and determining whether the related genes can be transmitted horizontally (Rodrıǵuez-Serrano et al, 2018;Toropov et al, 2020;Zhou et al, 2021).…”
Section: Limitations Challenges and The Way Forwardmentioning
confidence: 99%